Living with Uncertainty: Older Persons’ Lived Experience of Making Independent Decisions over Time - Agneta Breitholtz; Ingrid Snellman; Ingegerd Fagerberg (Nursing Research and Practice)
The aim of the study was to illuminate the meaning of older persons’ independent decision making concerning their daily care. Autonomy when in care is highly valued in the western world. However, research shows that autonomy can give rise to problematic issues. The complexity of independence and dependence for older people when living at home with help has also been highlighted. In Sweden, older people are increasingly expected to live at home with help from municipal home care services, and study into this aspect of care is limited. This study is a part of an ongoing project and has a qualitative life world perspective. Audiotaped narrative interviews were conducted and analysed using a phenomenological hermeneutic method. Findings revealed a main theme: “living with uncertainty as to how to relate one’s own independence and dependence with regard to oneself, and others.” This involves a constant process of relating to one’s independence controlled by others or oneself, and adjusting one’s independence and dependence with regard to oneself and others. The conclusion is that professional carers need to acknowledge the changing vulnerability of dependent older persons over time. The implication is a relational approach to autonomy beyond the traditional individualistic approach.